The Concept of Women’s Dress in Tafsir Nusantara: A Comparative Study of Four Indonesian Exegeses - Tri Hermawan; Putri Rafa Salihah; Muhammad Hafizh (Ulumuna, 2017)
This research aims to compare four Qur’anic commentaries on the verses regarding women’s dress code. They are taken from the Indonesian Quranic commentaries representing different time i.e the classical era, medieval era and contemporary era. They are Tarjumān al-Mustafīd, Tafsīr Qur’ān Karīm, Tafsīr Al-Azhar, and Tafsīr al-Miṣbāḥ. The purpose of this research is to explain how the verse regarding women’s dressing are interpreted in these four works and how such interpretation influence the concept of women’s dressing. This library research relies its data mainly on Indonesian Quranic commentaries and on other related literatures as the secondary supporting data. This uses language aproachment to find the meaning of the main words on each verses. They are then understood comparatively to reveal different interpretation and the factors that cause such differences. This study shows that there are three concept of woman’s dressing based on each interpretation, (1) the clothes that cover whole body including the face and the palm of hand, (2) the clothes that cover whole body except the face and palm of hand, (3) the respectfull clothes that do not cover the part of the head.